Selbstansaugende rotierende Sonde zur Entnahme von partikelfreien Gasproben aus Prozessgasen. Issue 12 (2nd October 2013) - Mescher, Axel; Thönes, Martin; Walzel, Peter
<x xml:space="preserve">Abstract</x> A filtration system for keeping the analytics free of particles is usually required for inline characterization of particle‐laden process gasses. Additionally gas pumps may be needed for overcoming the pressure drop of filter element and filter cake. Consecutive reactions of process gas and filter cake may be disadvantageous for the quality of the gas analysis. A new probing apparatus is presented for extraction of particle‐free gas samples from particle‐laden process gasses. The probe combines the functionalities of a gas pump and a particle separator. While the gas is transported from process to analysis, particles are separated according to the principle of air classification.